The importance of museums in the tourist development and the motivations of their visitors: an analysis of the Costume Museum in Viana do Castelo - Vareiro, Laurentina Cruz (2020)
Purpose – This study reflects on heritage, culture and museums as vectors of the tourist development of a destination. Considering the challenges inherent in the efficient correlation of these three areas, this study intends to demonstrate the clear benefits resulting from knowledge sharing and effective cooperation. Design/methodology/approach – Based on the objectives outlined, the authors conducted a survey of the visitors of the Costume Museum, which was chosen for being one of the unmistakable icons identifying the cultural heritage of Viana do Castelo (Portugal). Findings – In an increasingly competitive tourist market, with demand resulting from growing specialization, the integration of museological spaces as patrimonial and cultural elements in the supply of tourist destinations is an important factor in differentiation and development. Research limitations/implications – To enhance the importance of the Costume Museum in the process of the tourist development of the city, it is fundamental to define a clear strategy for attracting and responding to the greatest demand from cultural tourists who are increasingly interested in actively participating in learning experiences. It is believed that a larger sample could strengthen the conclusions, eventually more relevant and closer to the reality. Practical implications – The results show that visitors to the Costume Museum very positively evaluated the museum with regard to several factors covered in this study. However, there is a great dependence on school visits. On the other hand, lower qualitative evaluations were made by older age groups and those with higher academic degrees, although the evaluations remain positive. Social implications – The paper presents museums as a possible factor in tourism development and social inclusion, advancing practical measures aimed at social justice through a fairer distribution of tourism revenues and the defense of historic centre residents’ way, and quality, of life. Originality/value – This paper examines the importance of the Costume Museum in the tourist development of Viana do Castelo (Portugal). This study reflects on heritage, culture and museums as vectors of the tourist development of a destination. Particular attention is given to visitors’ motivations for visiting and their opinions about the quality of service, satisfaction and loyalty regarding this museum.